Surface Optimization of Noble‐Metal‐Free Conductive [Mn1/4Co1/2Ni1/4]O2 Nanosheets for Boosting Their Efficacy as Hybridization Matrices - Nam Hee Kwon; Se‐Jun Kim; Tae‐Ha Gu; Jang Mee Lee; Myung Hwa Kim; Dooam Paik; Xiaoyan Jin; Hyungjun Kim; Seong‐Ju Hwang (Advanced Science)
Abstract Conductive 2D nanosheets have evoked tremendous scientific efforts because of their high efficiency as hybridization matrices for improving diverse functionalities of nanostructured materials. To address the problems posed by previously reported conductive nanosheets like poorly‐interacting graphene and cost‐ineffective RuO2 nanosheets, economically feasible noble‐metal‐free conductive [MnxCo1−2xNix]O2 oxide nanosheets are synthesized with outstanding interfacial interaction capability. The surface‐optimized [Mn1/4Co1/2Ni1/4]O2 nanosheets outperformed RuO2/graphene nanosheets as hybridization matrices in exploring high‐performance visible‐light‐active (λ >420 nm) photocatalysts. The most efficient g‐C3N4–[Mn1/4Co1/2Ni1/4]O2 nanohybrid exhibited unusually high photocatalytic activity (NH4+ formation rate: 1.2 mmol g−1 h−1), i.e., one of the highest N2 reduction efficiencies. The outstanding hybridization effect of the defective [Mn1/4Co1/2Ni1/4]O2 nanosheets is attributed to the optimization of surface bonding character and electronic structure, allowing for improved interfacial coordination bonding with g‐C3N4 at the defect sites. Results from spectroscopic measurements and theoretical calculations reveal that hybridization helps optimize the bandgap energy, and improves charge separation, N2 adsorptivity, and surface reactivity. The universality of the [Mn1/4Co1/2Ni1/4]O2 nanosheet as versatile hybridization matrices is corroborated by the improvement in the electrocatalytic activity of hybridized Co−Fe‐LDH as well as the photocatalytic hydrogen production ability of hybridized CdS.